2023
DOI: 10.1002/ange.202311533
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cytochrome P450 Catalyzed Post‐translational Macrocyclization of Ribosomal Peptides**

Bei‐Bei He,
Jing Liu,
Zhuo Cheng
et al.

Abstract: Ribosomally synthesized and post‐translationally modified peptides (RiPPs) are a fascinating group of natural products that exhibit diverse structural features and bioactivities. P450‐catalyzed RiPPs stand out as a unique but underexplored family. Here, we introduce a rule‐based genome mining strategy that harnesses the intrinsic biosynthetic principles of RiPPs, including the co‐occurrence, co‐conservation, and interactions between precursors and P450s, successfully facilitating the identification of diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…11 Exceptional transformations catalyzed by RiPP enzymes result in diverse structural moieties 10 possessing antimicrobial, antiviral, antifungal, herbicidal, cytotoxic, anticancer, and other activities. 12-14 With nearly 50 reported structural classes, defined by the post-translational modification(s) installed, RiPP biosynthesis is a highly productive arena for the discovery of new enzyme chemistry, 15-29 identification of versatile bioengineering catalysts, 30-33 and isolation of structurally exotic compounds with unprecedented biological modes of action. 34,35 While tools like AlphaFold have provided high quality structures for millions of enzymes, 36 a major unsolved challenge is the determination of enzyme function.…”
Section: Introductionmentioning
confidence: 99%
“…11 Exceptional transformations catalyzed by RiPP enzymes result in diverse structural moieties 10 possessing antimicrobial, antiviral, antifungal, herbicidal, cytotoxic, anticancer, and other activities. 12-14 With nearly 50 reported structural classes, defined by the post-translational modification(s) installed, RiPP biosynthesis is a highly productive arena for the discovery of new enzyme chemistry, 15-29 identification of versatile bioengineering catalysts, 30-33 and isolation of structurally exotic compounds with unprecedented biological modes of action. 34,35 While tools like AlphaFold have provided high quality structures for millions of enzymes, 36 a major unsolved challenge is the determination of enzyme function.…”
Section: Introductionmentioning
confidence: 99%
“…130 Subsequent work applied the same workflow to P450s, which revealed a C−O−C ether cross-link between C2 of His i and C2 of His i+2 formed by SgrB (WP_051865888.1) (Figure 8B). 132 The authors also identified the enzymes responsible for forming the C−N cross-link between C7 of Trp i and N1 of Trp i+3 in cihunamide 76 and the rare C−C cross-link between C3 of Tyr i and C5 of Trp i+2 observed previously in pseudosporamide. 133 A peptide−P450 multilayer SSN was constructed to analyze the coconservation of substrate and enzymes, and along with AlphaFold-Multimer substrate− enzyme docking, 64,134 enhanced the accuracy of precursor peptide prediction.…”
Section: Using Prevalent Elements In Ripp Biosynthesis As Bioinformat...mentioning
confidence: 85%
“…Mutation of the His residue in the precursor peptide to a Tyr residue resulted in a linkage between C3 of Tyr i and C β of Ala i+2 (Figure B) . Subsequent work applied the same workflow to P450s, which revealed a C–O–C ether cross-link between C2 of His i and C2 of His i+2 formed by SgrB (WP_051865888.1) (Figure B) . The authors also identified the enzymes responsible for forming the C–N cross-link between C7 of Trp i and N1 of Trp i+3 in cihunamide and the rare C–C cross-link between C3 of Tyr i and C5 of Trp i+2 observed previously in pseudosporamide .…”
Section: Using Prevalent Elements In Ripp Biosynthesis As Bioinformat...mentioning
confidence: 97%
“…In recent studies, our research focused on genomics-guided discovery of RiPP antibiotics, resulting in the discovery of antagonistic lanthipeptide from archaea and narrow-spectrum class II bacteriocins from the human microbiome 18,19 . Moreover, applying rule-based genome mining strategies, we successfully revealed previously hidden peptidases 20 and untapped post-translational modification (PTM) enzymes 21,22 for RiPP antibiotic biosynthesis. However, the challenge remains in the prioritization of BGCs of interest and the robust linking of metabolites to their corresponding BGCs prior to time-consuming isolation and identification.…”
Section: Introductionmentioning
confidence: 99%